A Study of Motivation Factors Among Indian Entrepreneurs in Klang Valley - Bawani, Krishnasamy (2012)
The purpose of this research is to study the view points of Indian entrepreneurs in the Klang Valley area of Peninsular Malaysia, especially from the perspective of motivation factors, which influence their decision to start up a their own business. This study is undertaken to identify the basic demographic variables, business characteristics and major problems that occur during the start up stage and its present business operation among the Indian entrepreneurs. This study also examines motivation factors that motivate Indian entrepreneurs to start up a new business. The primary data collected through questionnaires were distributed to 250 Indian entrepreneurs. “Statistical Package for the Social Sciences” (SPSS) was used for data analysis: description analysis, descriptive, inferential and t-test were used to explain the background, motivation and to test the hypothesis. This study shows that the majority of the Indian entrepreneurs involved in retail services and trading business and are sole sole-founders of the business. Major problems in their business lies in management, finance, government regulations, technological expertise are also assumed to be the major problems and personal problems in term of financial is included also. To understand the motivator, a descriptive and inferential analysis has performed that the recognition and personal development is most important to start up a business, others are accommodation, satisfaction, communitarianism and also family tradition plays an important role as a motivator. In general, results of this study would help to gain more understanding on the culture and background of Indian entrepreneurs. Finally, this study also gives a useful tool to entrepreneurs, business associations, researchers and policy makers to improve entrepreneurial activities in Malaysia.